Приморские регионы Арктики: проблемы и перспективы социально-экономического развития - Sorokina, N.Y.; Сорокина, Н. Ю. (Siberian Socium, 2018)
This article indicates the main tendencies of social and economic dynamics of the coastal regions of the Arctic. These are the territories, currently connected with the prospects of Russia’s policy towards China as a new economic center of the world economy. The authors show that the Arctic’s seaside position is an objective factor of district formation, although not all coastal territories use their competitive advantages effectively. The main features of the coastal regions include availability of port activity in the sectoral structure of the regional economy, developed marine industrial fisheries, and a significant contribution of the coastal infrastructure to the regional development. The analysis employs the index method by calculating the integrated indicator of socio-economic development of the region as an aggregate of the indicator of general economic development, as well as socio-demographic and resource-sector indicators. The results reveal that the key sources of growth for the coastal regions of the Arctic remain to be the branches of the mining complex. This paper lists the positive dynamics of specific types of activities that determine the competitiveness of maritime territories as port activity, fishing industry, recreation, and tourism. The authors prove that, despite the positive dynamics of economic development, the coastal regions of the Arctic have so far failed to ensure a decent standard of living for the population and stimulate the development of social infrastructure at the level of the regions of the European part of Russia. As a positive trend, there has been a reduction in the differentiation of the Arctic coastal regions of Russia in terms of socio-economic development indicators. The authors suppose that, in the coming years, the coastal regions of Russia may play a significant role in the country’s economy, determining the potential for its integration into the world economic system and competitive advantages in the development of the resources of the World Ocean. Обозначены основные тенденции социально-экономической динамики приморских регионов Арктики – территорий, с которыми в настоящее время связаны перспективы движения России к новому центру мировой экономики – Китаю. Показано, что приморское положение – это объективный фактор районообразования, хотя не все приморские территории эффективно используют конкурентные преимущества, обусловленные имеющимся у них выходом к морям. Характерными чертами приморских регионов являются: наличие в отраслевой структуре региональной экономики портовой деятельности, развитое морское промышленное рыболовство, существенный вклад береговой инфраструктуры в региональное развитие. Анализ осуществлен с использованием индексного метода путем расчета комплексного показателя социально-экономического развития региона как агрегата показателя общеэкономического развития, социально-демографического показателя и ресурсно-отраслевого показателя. Выявлено, что ключевым источником роста приморских регионов Арктики по-прежнему выступают отрасли добывающего комплекса. Отмечена позитивная динамика специфических видов деятельности, определяющих конкурентоспособность приморских территорий: портовой деятельности, рыбной промышленности, рекреации и туризма. Аргументировано, что, несмотря на позитивную динамику экономического развития, приморским регионам Арктики до сих пор не удалось обеспечить достойный уровень жизни населения и стимулировать развитие социальной инфраструктуры на уровне регионов европейской части России. В качестве позитивной тенденции отмечено сокращение дифференциации арктических приморских регионов страны по показателям социально-экономического развития. Сформулированы выводы, согласно которым в ближайшие годы приморские регионы России будут определять потенциал интеграции страны в мировую экономическую систему и ее конкурентные преимущества при освоении ресурсов Мирового океана.